(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
This paper is noteworthy because it investigates a novel method for comparing the expectations of stochastic models in fuzzy contexts. Actuarial science and economics both depend on stochastic models. Understanding the novel concepts of stochastic comparison of stochastic models based on the exponential order is the main advantage of this study. We solved the preservation properties and theorem, created a new definition, and put the fuzzy mean inactive time order definition into practice. Stochastic models are handled in a variety of applications.